A note on Gordan's theorem over cone domains - Brad Skarpness; V. A. Sposito (International Journal of Mathematics and Mathematical Sciences)
This note presents a proof of Gordan's Theorem over general closed, convex cone domains which follows in a natural way appealing to the standard definitions of closed convex cones and their respective polar cones.